Platelet Aggregation Following Defibrination with Ancrod - Lawrence Slade, C; Abe Andes, W; Mason, Arthur D., Jr. (Thrombosis and Haemostasis, 1976)
In vitro platelet aggregation was studied in dogs following defibrination with Ancrod. There was marked inhibition of aggregation immediately after defibrination. A gradual return toward normal aggregation was observed over the 96 hours study period, but aggregation was still abnormal at 96 hours after defibrination. There was an inverse and highly significant correlation between aggregation and fibrin degradation product level. Fibrinogen was not measurable after defibrination for the entire study period. Aggregation was thus independent of fibrinogen concentration in this study.